1995
DOI: 10.1007/bf00184085
|View full text |Cite
|
Sign up to set email alerts
|

Modelling series of visual fields to detect progression in normal-tension glaucoma

Abstract: A linear model of the pointwise sensitivity values against time of follow-up can provide a framework for detecting and forecasting glaucomatous field progression. Linear modelling allows the clinically important rate of sensitivity loss to be estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 9 publications
3
70
0
1
Order By: Relevance
“…This question cannot easily be solved, because the phenotype of continuous loss may resemble that of stepwise progression, and vice versa, due to perimetric variability and discrete sampling. Both types of progression have been reported [6,7]. The current study showed adaptive testing to be the preferred approach for continuous loss; an earlier study yielded the same conclusion for stepwise progression [4].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This question cannot easily be solved, because the phenotype of continuous loss may resemble that of stepwise progression, and vice versa, due to perimetric variability and discrete sampling. Both types of progression have been reported [6,7]. The current study showed adaptive testing to be the preferred approach for continuous loss; an earlier study yielded the same conclusion for stepwise progression [4].…”
Section: Discussionsupporting
confidence: 70%
“…Whether glaucomatous deterioration is a stepwise or a continuous process has not yet been settled. Stepwise progression has been reported, but arguments in favour of continuous loss have also been published [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although trend analysis does make the assumption that change can be expressed linearly, this seems appropriate as it provides the best 'fit' in untreated visual field series. 71 Analysis using pointwise linear progression agrees well with expert observers. 72 The ability to subdivide the visual field into progressing sections rather than rely on median values is an advantage, for the latter will overlook small but significant changes even though the effects of lens opacities have been removed.…”
Section: Eyesupporting
confidence: 56%
“…Trend analysis suggests that the linear model is the best 'fit', at least for NTG (Figure 3). 8 Using the linear model, it has been shown that the rate of progression in untreated NTG patients varies greatly despite similar ages and MD at baseline.…”
Section: Resultsmentioning
confidence: 99%